Job profile of non-medical practitioners: a cross-sectional study from the health service perspective - Kattge, Stefanie; Götz, Katja; Glassen, Katharina; Steinhäuser, Jost (Complementary medicine research, 2017)
Background: The demand for complementary and alternative medicine (CAM) is rising. The German ‘Heilpraktiker' is a non-medical naturopathic practitioner (NMNP) providing CAM. Their numbers are rising constantly; however, little is known about their practices and reasons for consultation and on what kind of treatment they offer. Methods: All 1,096 NMNPs in the German federal state of Schleswig-Holstein were invited to participate in a questionnaire study to gain first insights into their nearly unexplored group setting. Results: A total of 262 NMNPs responded to the itemized questionnaire; 60 answered the questionnaire suggested for non-responders. Out of the 262 NMNPs, 211 (81%) were female. The average age was 53 years. Analyzing the most frequent reasons for consultation, 68.2% were found to be general and unspecified reasons, followed by psychological causes (64.1%) and musculoskeletal complaints (53.1%). About 68% of the participants treat conditions of pain. The most commonly used group of methods was found to comprise para-medicinal procedures. Conclusions: Our analysis gives first insights into the occupational profile of the German NMNPs, their scope of activities and treatment methods. It is a first step towards health service research that might provide a basis for further studies.
Gesehen am 16.07.2018